Examining the effect of different platforms of digital promotion on customer satisfaction in transient houses in Vigan City - Encarnacion, Marie Joy; RAPISURA, ELA MAE (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2025)
The research explored promotional strategies to determine their effect on customer satisfaction in Vigan City transient houses. The research investigated the impact of online presence and digital marketing on attracting guests while improving their experience. The research used a quantitative approach to gather data from transient house guests who assessed their digital marketing channel experiences, booking convenience, and satisfaction levels. The analysis showed that Facebook and Instagram operated as the primary social media platforms through which customers discovered and interacted with the business. Statistical analysis of digital promotional strategies revealed important relationships between these strategies and customer satisfaction ratings. The most effective promotional strategies included advertisements that fulfilled customer needs, straightforward online information, simple booking procedures, and social media promotion. Social media advertisements, customer reviews, and promo codes were promotional tools to deliver information to guests. The highest outcomes occurred when digital promotional strategies were integrated with high-quality service delivery. The study indicates that transient houses must update their digital marketing approach by improving their social media presence and adopting AI-based customer service to deliver personalized wait time solutions. Combining advanced digital marketing strategies with outstanding service delivery will drive customer satisfaction and brand loyalty while enabling transient houses to succeed against hospitality industry competitors. Keywords: promotional strategies, customer satisfaction, transient houses, online presence, digital marketing